2010
DOI: 10.1086/656408
|View full text |Cite
|
Sign up to set email alerts
|

Early Oseltamivir Treatment of Influenza in Children 1–3 Years of Age: A Randomized Controlled Trial

Abstract: Oseltamivir treatment started within 24 hours of symptom onset provides substantial benefits to children with influenza A infection. Clinical trials registration. ClinicalTrials.gov identifier: NCT00593502.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 35 publications
5
129
1
Order By: Relevance
“…Almost no children with influenza were treated with oseltamivir, even though the drug is well tolerated in children and treatment started within 24 hours of symptom onset provides substantial benefits to children with influenza A infection 24. It is urgent to make oseltamivir more widely available for influenza patients, and educate Chinese clinicians about the clinical benefit of early oseltamivir treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Almost no children with influenza were treated with oseltamivir, even though the drug is well tolerated in children and treatment started within 24 hours of symptom onset provides substantial benefits to children with influenza A infection 24. It is urgent to make oseltamivir more widely available for influenza patients, and educate Chinese clinicians about the clinical benefit of early oseltamivir treatment.…”
Section: Discussionmentioning
confidence: 99%
“…39 However, timely administration of oseltamivir has been associated with shorter hospitalizations among critically ill children, 40 faster resolution of illness (1.0-1.5 days in healthy children), and less parental work absenteeism. [41][42][43] Also, 43% to 44% fewer outpatient children who received oseltamivir within 48 hours of influenza symptoms developed acute otitis media. [43][44][45] When the 2009 pandemic influenza began in the United States in mid-April 2009, recommendations were made for expanded use of antiviral medications and were associated with increased antiviral usage 46 ; thus, usage patterns from before versus after the 2009 pandemic may differ.…”
Section: Figurementioning
confidence: 99%
“…Data regarding the use of oseltamivir, an inhibitor of the infl uenza enzyme neuraminidase, 5 have been confl icting with some studies showing shortened duration and severity of seasonal infl uenza infection in adults and children including patients with high-risk conditions. [6][7][8][9][10][11][12][13][14][15][16] However, 2 recent meta-analyses have suggested that although oseltamivir decreases the duration of symptoms or the time to fi rst alleviation of symptoms, it did not decrease the rate of provider-diagnosed pneumonia or hospitalization. 17,18 These new fi ndings arise in part from the fact that 9 randomized controlled trials sponsored by manufacturers had not previously been published in full even though patients agreed to be subjects in a study of what was an experimental medication.…”
Section: Hospital Readmissions Among Children With H1n1 Infl Uenza Inmentioning
confidence: 99%